Presence of the dissociative subtype of PTSD does not moderate the outcome of intensive trauma-focused treatment for PTSD. Issue 1 (1st January 2018) - Zoet, Harmen A.; Wagenmans, Anouk; van Minnen, Agnes; de Jongh, Ad
ABSTRACT: Background : There is a widely-held belief in the trauma field that the presence of dissociative symptoms is associated with poor treatment response. However, previous research on the effect of dissociation in treatment outcomes pertained to specific patients and trauma populations. Objective : To test the hypothesis that the presence of the dissociative subtype of PTSD (DS) would have a detrimental effect on the outcome of an intensive trauma-focused treatment programme. Methods : PTSD symptom scores (Clinician Administered PTSD Scale [CAPS] and PTSD Symptom Scale Self-Report [PSS-SR]) were analysed using the data of 168 consecutive patients (70.6% female) who had been exposed to a wide variety of multiple traumas, including childhood sexual abuse, and of whom 98.2% were diagnosed with severe PTSD (CAPS > 65). Most of them suffered from multiple comorbidities and 38 (22.6%) met the criteria for DS. They took part in an intensive trauma-focused treatment programme for PTSD. Pre- and post-treatment differences were compared between patients with and without DS. Results : Large effect sizes were achieved for PTSD symptom reduction on CAPS and the PSS-SR, both for patients with DS and those without. Although patients with DS showed a significantly greater PTSD symptom severity at the beginning, and throughout, treatment, both groups showed equal reductions in PTSD symptoms. Of those who met the criteria for DS, 26 (68.4%) no longer fulfilled the criteria for this classification after treatment. Conclusion : The results provide no support for the notion that the presence of DS negatively impacts trauma-focused treatment outcomes. Accordingly, PTSD patients with DS should not be denied effective trauma-focused treatments.